Effects of the air pollution dynamics on semen quality and sperm DNA methylation in men living in urban industrial agglomeration - Vozdova, Miluse; Kubickova, Svatava; Kopecka, Vera; Sipek, Jaroslav; Rubes, Jiri (Environmental and molecular mutagenesis, 2022)
Human populations living in urban industrial regions of developed countries are exposed to high levels of environmental pollutants. The reproductive consequences of the exposure to air pollution can be monitored through semen analysis and molecular methods. In this study, we tested the possible impact of seasonal changes in the level of air pollution on the semen quality and sperm DNA methylation of 24 men living and working in the industrial agglomeration of Ostrava (Czech Republic). The study participants were healthy non-smokers. The study group was homogeneous regarding their profession, moderate alcohol consumption, no drug abuse and no additional exposure to chemical toxicants. We performed targeted methylation next generation sequencing (NGS) using Agilent SureSelect Human Methyl-Seq and Illumina NextSeq 500 platform to analyze semen samples collected repeatedly from the same men following the season of high (winter) and low (summer) air pollution exposure. We did not detect any adverse effects of the increased exposure on the semen quality; neither we found any difference in average sperm DNA methylation between the two sampling periods. Our search for differentially methylated CpG sites did not reveal any specific CpG methylation change. Our data indicate that the seasonal changes in the level of the air pollution probably do not have any substantial effect on sperm DNA methylation of men living in the highly polluted industrial agglomeration for a long period of time.
Keywords: Spermatozoa; znečištění ovzduší; lidé; Air Pollution; Female; mužské pohlaví; Industry; Semen Analysis; Male; průmysl; spermie; analýza spermatu; DNA Methylation; ženské pohlaví; metylace DNA; Humans